$k$-smoothness: an answer to an open problem - Wójcik, Paweł (MATHEMATICA SCANDINAVICA, 2018)
The aim of this paper is to characterize the $k$-smooth points of the closed unit ball of $\mathcal{K}(\mathcal{H}_1;\mathcal{H}_2)$. In this paper we also answer a question posed by A. Saleh Hamarsheh in 2015.